Elemental determination of austenitic stainless steel alloy used as biomaterial by neutron activation analysis - Lilian Ninoska Muriel Braguin; Caio Almeida Justino; Isolda Costa; Mitiko Saiki (Brazilian Journal of Radiation Sciences)
Austenitic stainless steel alloys, mainly those produced according to ISO 5832-1, have received much attention due to their promising characteristics to be used as biomaterials. The aim of this study was to establish the proper conditions of neutron activation analysis (NAA) in order to determine chemical elements in a sample of ISO 5832-1 stainless steel. These determinations are of great interest for further evaluation of its corrosion resistance and of cytotoxicity of corrosion products. For the analyses, chips of ISO 5832-1 austenitic stainless steel were obtained. Aliquots of this material were weighed in polyethylene involucres and irradiated together with synthetic element standards at the IEA-R1 nuclear research reactor. Short and long irradiations were carried out using thermal neutron flux of about 4.5 x 1012 n cm-2 s-1. Quality control of the results was performed by analyzing two certified reference materials (CRMs). The elements concentrations of Cr, Cu, Mn, Mo and Ni obtained in the ISO 5832-1 austenitic alloy are within the specification values of this material. Besides, the elements As, Co, V and W were determined in this alloy. The sensitivity of the technique was verified by the determination of detection and quantification limits. In the case of CRMs, their results presented precision and accuracy for most of elements with relative standard deviations and relative errors lower than 15 %. Results obtained in this study demonstrated the viability of applying NAA in the analysis of the ISO 5832-1 stainless steel alloy.